Efforts to Solve Absenteeism by Employees at Companies According to the Labor Law Number 13 of 2003 - Fuvut Wardani; Sri Anggraini Kusuma Dewi (Faculty of Law, Merdeka University Surabaya, Indonesia, 2023)
The aim of this research is to describe and identify regarding an in-depth study and ensuring that there are no acts of absenteeism in accordance with the Labor Law Number 13 of 2003. This research method uses normative juridical which means that what is produced is deviation not from theory, namely an approach by examining or studying a statutory regulation . The results of the research based on the applicable laws and regulations, namely Law Number 13 of 2003 concerning Manpower Article 168, legally fulfill the elements of Termination of Employment for reasons of absenteeism who are qualified to resign which contains 3 (three) elements including There is a Job, There is a Wages/Salary and There's an Order.